2006
DOI: 10.1111/j.1471-4159.2006.04223.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of α‐glycerophosphate‐evoked H2O2 generation in brain mitochondria

Abstract: Characteristics of reactive oxygen species (ROS) production in isolated guinea-pig brain mitochondria respiring on aglycerophosphate (a-GP) were investigated and compared with those supported by succinate. Mitochondria established a membrane potential (DY m ) and released H 2 O 2 in parallel with an increase in NAD(P)H fluorescence in the presence of a-GP (5-40 mM). H 2 O 2 formation and the increase in NAD(P)H level were inhibited by rotenone, ADP or FCCP, respectively, being consistent with a reverse electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 63 publications
5
74
1
3
Order By: Relevance
“…It is important to note that there was no difference in the levels and activity of CYP450 2E1 in liver from lean and ethanol-naïve ob/ob mice [69]. Mitochondrial ROS generation has also been ascribed to several matrix enzymes including α-ketoglutarate dehydrogenase [71,72] and α-glycerophosphate dehydrogenase [73]. Whether these enzymes contribute to increased ROS production during the conditions of alcohol and obesity induced fatty liver disease is not known, however it is predicted that higher rates of ROS in mitochondria during these pathologies will negatively affect mitochondrial and cellular function by oxidative modification and alteration in redox-sensitive signaling pathways.…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 99%
“…It is important to note that there was no difference in the levels and activity of CYP450 2E1 in liver from lean and ethanol-naïve ob/ob mice [69]. Mitochondrial ROS generation has also been ascribed to several matrix enzymes including α-ketoglutarate dehydrogenase [71,72] and α-glycerophosphate dehydrogenase [73]. Whether these enzymes contribute to increased ROS production during the conditions of alcohol and obesity induced fatty liver disease is not known, however it is predicted that higher rates of ROS in mitochondria during these pathologies will negatively affect mitochondrial and cellular function by oxidative modification and alteration in redox-sensitive signaling pathways.…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 99%
“…Most commonly, combinations of complex I and complex III inhibitors (e.g. rotenone and myxothiazol) have been used to prevent production of superoxide from complex I during reverse electron transport and from the outer Q-binding site of complex III (site III Qo ) (21)(22)(23)25). These studies identified mGPDH as a likely site of mitochondrial superoxide production and provided evidence that mGPDH generates superoxide to both sides of the mitochondrial inner membrane (20).…”
mentioning
confidence: 97%
“…The bulk of this H 2 O 2 production is commonly attributed to superoxide generation from site III Qo , because it is sensitive to the site III Qo inhibitor myxothiazol (addition iv). It is this condition, oxidation of glycerol 3-phosphate in the presence of rotenone and myxothiazol, inhibitors of sites I Q and III Qo , that has previously been taken to define H 2 O 2 production specifically from mGPDH (20,22,24).…”
Section: Measurement Of Total Superoxide and H 2 Omentioning
confidence: 99%
“…This could indicate ROS release at complex I (via RET) but also at complex III (Chowdhury et al 2005;Drose and Brandt 2012;Tretter et al 2007). Of note, upon TCR triggering, complex III seems to be activated by a stable modification in a PKC-dependent manner (Kaminski et al 2012b).…”
Section: The Enzymatic Sources Of the Oxidative Signalmentioning
confidence: 99%
“…Activated GPD2 directly reduces ubiquinone and releases ROS either at the complex I via RET or itself. Moreover, since complex III and IV inhibitors enhance GPD2-dependent ROS production (Chowdhury et al 2005;Lambert and Brand 2009;Miwa et al 2003;Tretter et al 2007), complex III involvement is also possible. Therefore, GPD2 plays a major role for T-cell activationinduced ROS release by connecting enhanced glycolysis with hyper-reduction of the mitochondrial respiratory chain (Fig.…”
Section: The Enzymatic Sources Of the Oxidative Signalmentioning
confidence: 99%